2021
DOI: 10.3390/healthcare9020201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Physical and Mental Fatigue among Female Hospital Nurses: The Korea Nurses’ Health Study

Abstract: Nurses often experience work-related physical and mental fatigue. This study sought to identify the levels of physical and mental fatigue present among Korean female nurses and discern factors influencing their onset. This cross-sectional study analyzed data from the Korea Nurses’ Health Study (KNHS). A total of 14,839 hospital nurses were assessed by hierarchical regression analysis. The mean scores of physical and mental fatigue were 12.57 and 5.79 points, respectively. After adjusting for confounding variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
(40 reference statements)
2
27
0
5
Order By: Relevance
“…The findings also demonstrated that age and gender were associated with all fatigue subscales and total fatigue. Some previous studies have also revealed that age could contribute to the development of fatigue in nurses [ 48 , 49 ]. The current findings regarding the association between gender and fatigue were similar to those of the Thompson study [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings also demonstrated that age and gender were associated with all fatigue subscales and total fatigue. Some previous studies have also revealed that age could contribute to the development of fatigue in nurses [ 48 , 49 ]. The current findings regarding the association between gender and fatigue were similar to those of the Thompson study [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these elements potentially increase nurses' risk of developing pandemic fatigue, adversely affecting their overall health and clinical performance and eventually leading to poor nursing care provision and poorer patient outcomes (del Carmen Giménez-Espert et al, 2020;. Studies have demonstrated that a greater proportion of nurses, particularly those directly taking care of COVID-19 patients, experienced a significant amount of fatigue during the peak of the pandemic (Jang et al, 2021). The incidence of moderate-to-high fatigue levels during the pandemic ranged from 35.06% to 72.2%, with more nurses experiencing physical fatigue than mental fatigue (Zhan et al, 2020;Zou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies about employees working in hospitals were focused on nurses, physicians, and other medical professionals, but did not include administrative staff or general staff. Moreover, the focus of research often concerned burnout, demoralization, and fatigue [6][7][8]12]. In Kenya, Muthuri et al concerned health-related quality of life among healthcare workers to develop and implement national policies and programs for healthcare works [13].…”
Section: Discussionmentioning
confidence: 99%
“…Medical institutions have to pay more attention to the importance of physical and mental health of medical staff because it is not only a simple self-care issue, but also affects the quality of patient care. Previous studies on medical and health working scenarios focused heavily on their negative impacts such as high work pressure, emotional exhaustion, fatigue, and low job satisfaction among hospital employees, and rarely explored them from a positive perspective except quality of life [11][12][13][14]. In addition, most studies focused on nursing staff rather than all hospital employees.…”
Section: Introductionmentioning
confidence: 99%